Light years : conceptual art and the photograph, 1964-1977 - Godfrey, Mark.; Art Institute, Chicago (Chicago, IL : Art Institute of Chicago, 2011)
Contents:##- The unfixed photograph / Matthew S. Witkovsky##- Across the universe / Mark Godfrey##- Uninteresting pictures: photography and fact at the end of the 1960s / Joshua Shannon##- Hazarded into the blue: John Baldessari and photography in the early 1970s / Robin Kelsey##- Rona Barrett's Hollywood / Allen Ruppersberg##- Art is the copy of art: Italian photography in and after arte povera / Giuliano Sergio##- Reconfiguring representation: mechanical reproduction and the human figure in conceptual art / Anne Rorimer.
Published in conjunction with an exhibition organized by and presented at the Art Institute of Chicago from December 13, 2011, to March 11, 2012
boek